Kesempurnaan Allah Sebagai Dasar Edukasi Pola Hidup Kekristenan - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
Not many Christian lifestyle education that clearly captures the meaning of the call to life to be perfect like the Father in the practice of daily life as believers. So that the writing of this journal is intended to dissect the meaning of the vocation as well as the commandment of how the consequences of living standards as followers of Christ Jesus are. With a complete and practical explanation, it is hoped that believers can understand and take a commitment to live a perfect Christian lifestyle like the Father. This study uses a literature review method, namely by analyzing the perfect concept such as the Father as a standard concept framework and Christian lifestyle as a direction for the development and Christian Religious Education. The results of this study demonstrate the concept and implications for the direction of Christian education in generating and shaping Christian life toward perfection as the Father there are at least nine applications that can be done to guide the pattern of the Christian life of believers, namely: First,Has intelligence and rigor spiritual . Second, Life is blameless and blameless. Third, live by fulfilling God's demands. Fourth, live with quality faith. Fifth, Life like Jesus. Sixth, live according to God's will. Seventh, a life pleasing to God. Eighth, Live with a new mindset. Ninth, Live with extraordinary behavior.